Portal matter, kinetic mixing, and muon g − 2 - George N. Wojcik; Lisa L. Everett; Shu Tian Eu; Ricardo Ximenes (Physics Letters B, 2023)
We present a minimal construction using leptonic portal matter that addresses the muon g−2 anomaly. While the chiral enhancement mechanism is reminiscent of that of fermiophobic Z′ gauge models, the parameter space motivated by the kinetic mixing/vector portal dark matter model paradigm is vastly different and can be readily explored in current and forthcoming experiments.